The effect of behavioral bias moderated by financial literacy, cognitive ability, and self-efficiency on stock investment decisions in youth generations - Dimas Tristiyono; Tafdil Husni; Fajri Adrianto (Enrichment : Journal of Management, 2023)
Employees in the Padang Sumatra V River Basin Office are under the Ministry of Public Works and Public Housing, where the majority of employees are young people who decide to invest in stocks as a guide and provision for their life which is obtained from capital gains and dividends that can be used for the future if the employment relationship is later abolished. and contracts that cannot be extended due to political affairs. Based on this, this study aims to analyze the effect of behavioral bias, cognitive ability, and self-efficacy on stock investment decisions with financial literacy as a moderator. Data comes from 137 younger generation employees who are collected through online structured questionnaires (Google Forms). Structured equation modeling with a partial least squares approach is adopted for data analysis. The results of the study show that behavioral bias and cognitive ability have a significant effect on stock investment decisions compared to self-efficacy not being a predictor of stock investment decisions and financial literacy does not weaken the relationship between behavioral bias and irrational stock investment decision making